Profil Darah dan Struktur Mikroanatomi Insang Belut Sawah (Monopterus albus Zuiew) Setelah Paparan Herbisida Paraquat Diklorida - maulaningrum, wulandari (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2023)
Abstract The paraquat dichloride herbicide is difficult to degrade biologically, and it is widely used in agricultural land, which is the habitat of rice field eels. The toxic effect of the paraquat dichloride herbicide in an environment can be seen from changes in the hematological values of an animals, one of which is the rice field eel. The aim of this research is to determine the hematological value and microanatomical structure of rice field eel gills after exposure to paraquat dichloride herbicide. This study used a randomized block design with four replications and five treatments: control, 1,5 ppm, 2,76 ppm, 4,14 ppm and 5,52 ppm. Exposure to paraquat dichloride herbicide at concentrations of 1,5 ppm, 2,76 ppm, 4,14 ppm, and 5,52 ppm a noticeable decrease over control of total erythrocytes, total leukocytes, hemoglobin levels, hematocrit values, MCV, MCH, and lymphocyte counts. The number of monocytes and neutrophils has also undergone noticeable improvements over control. The highest decrease in total leukocytes was 45% and in differential leukocytes the highest increase was in the number of neutrophils by 176%. Exposure to paraquat dichloride herbicides causes hypertrophy, hemorrhages, and fusion of rice eel gill filaments.